Integrating computer games in primary education for increased students’ QoE - Malinovski, Toni; Vasileva, Marina; Trajkovikj, Vladimir (Springer International Publishing, 2014)
Continuous improvement of the learning environment and pedagogical methodology are tasks that every educational program has to endure. This study explores integration of computer games in the primary educational program, their proper alignment with the learning curriculum, while creating powerful learning environment which increases student’s effectiveness and motivation to learn. The research methodology follows user-oriented approach while evaluating different variables in a computer game enhanced class, which impact the overall students’ Quality of Experience (QoE). A case study is conducted with a traditional and non-traditional class in several primary schools in Macedonia, students’ feedback is collected through surveys and the data set is analyzed according to the proposed methodology. Path analyses model is presented illustrating the relationships among several relevant variables in the class with a computer game and their connection to the students’ QoE.
Keywords: Computer Game, Primary Education, QoE, Learning, Evaluation, Path Analyses Model